Development and application of the adverse outcome pathway framework for understanding and predicting chronic toxicity: II. A focus on growth impairment in fish. (February 2015) - Groh, Ksenia J.; Carvalho, Raquel N.; Chipman, James K.; Denslow, Nancy D.; Halder, Marlies; Murphy, Cheryl A.; Roelofs, Dick; Rolaki, Alexandra; Schirmer, Kristin; Watanabe, Karen H.
Highlights: Development of AOPs for chronic toxicity helps identify alternative tests. Interference of chemicals with behavior can cause growth impairment in fish. Assessment of locomotion may be used to identify chemicals that may affect growth. Reallocation of energy resources induced by chemicals can cause growth impairment. Metabolic activity measures may be used to identify chemicals that may affect growth. Abstract: Adverse outcome pathways (AOPs) organize knowledge on the progression of toxicity through levels of biological organization. By determining the linkages between toxicity events at different levels, AOPs lay the foundation for mechanism-based alternative testing approaches to hazard assessment. Here, we focus on growth impairment in fish to illustrate the initial stages in the process of AOP development for chronic toxicity outcomes. Growth is an apical endpoint commonly assessed in chronic toxicity tests for which a replacement is desirable. Based on several criteria, we identified reduction in food intake to be a suitable key event for initiation of middle-out AOP development. To start exploring the upstream and downstream links of this key event, we developed three AOP case studies, for pyrethroids, selective serotonin reuptake inhibitors (SSRIs) and cadmium. Our analysis showed that the effect of pyrethroids and SSRIs on food intake is strongly linked to growth impairment, while cadmium causes a reduction in growth due to increased metabolic demands rather than changes in food intake. Locomotion impairment by pyrethroids is strongly linked to their effects on food intake and growth, while for SSRIs their direct influence on appetite may play a more important role. We further discuss which alternative tests could be used to inform on the predictive key events identified in the case studies. In conclusion, our work demonstrates how the AOP concept can be used in practice to assess critically the knowledge available for specific chronic toxicity cases and to identify existing knowledge gaps and potential alternative tests.